The conquest of Khūzistān: a historiographical reassessment - Robinson, C (Cambridge University Press, 2004)
The 'appendix' to a mid- to late seventh-century East Syriac history includes a detailed account of the conquest of Khūzistān by Muslim armies between c. 635 and 642. This article translates this section of the 'appendix' (along with another dealing with the conquest of Egypt), subjects it to detailed analysis and criticism, and compares it with Arabic accounts of the conquest of Khūzistān that survive in the much later historical and legal traditions. The results of this exercise - using an early and local source to control the Islamic tradition - is in some measure mixed, but some striking agreement suggests that the transmission of conquest history in early Islam was not as discontinuous as has been previously argued.